Flood Syndrome, Rare but Feared Complications - Laiq, Sobia; Ahmad, Nabeel; Yaqoob, Sadia (Journal of the Pakistan Medical Association, 2023)
Madam, I am writing to bring attention to a medical condition known as Flood Syndrome, a life-threatening occurrence characterized by the sudden rush of fluid following the spontaneous rupture of an umbilical hernia in individuals with long-standing ascites and end-stage liver disease. While uncommon, this syndrome poses a serious threat to patients' well-being. The umbilical hernia typically ruptures due to increased intra-abdominal pressure resulting from coughing, vomiting, straining during defecation, or an increased ascitic fluid volume (1). This syndrome's history dates back to 1901, when Johnson first described it, while the term "Flood Syndrome" was coined by Frank B. Flood in 1961 (2). Ascites, a common complication of liver cirrhosis, affects nearly half of the population with this condition. Large-volume ascites significantly impairs the patients' ability to perform daily activities. Approximately 20% of cirrhotic patients with ascites also develop an umbilical hernia. Flood Syndrome presents several potential complications, including cutaneous infections, skin necrosis or ulceration, peritonitis, hypotension, fluid imbalance, sepsis, and bowel incarceration (3). Despite its rarity, only a few case studies available on this topic, with the majority focusing on cases related to liver cirrhosis. An intriguing case presented by Murruste et al (5). highlights Flood Syndrome following right-sided heart failure, with no previous records of such a condition in connection with ascites primarily caused by right-sided heart failure. The optimal treatment for Flood Syndrome remains a matter of debate; however, research suggests that surgical intervention yields better outcomes compared to conservative treatment alone. Mortality rates can be as high as 60%-80% with conservative measures, while surgical hernia repair has a lower mortality rate of 6%-20% (4). Hence, raising awareness about Flood Syndrome and its associated risk factors is essential for improving patient outcomes and reducing the incidence of this life-threatening condition. Therefore, educate patients, particularly those with severe ascites due to liver cirrhosis to diligently follow up with their doctors and adhere to their prescribed medications to avoid such dreaded complications. Additionally, physicians should advise their patients to avoid heavy lifting, which can help prevent the formation of umbilical hernias. We can work towards more effective preventive measures and treatments.by fostering a better understanding of this syndrome among medical professionals and patients alike., Timely diagnosis and a multidisciplinary approach to treatment are vital in achieving the best possible outcomes in such cases. Together, we can make a significant impact in addressing this medical challenge.